2021
DOI: 10.1007/s10641-021-01115-6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal morphophysiological changes during the reproductive cycle of the tripletail fish Lobotes surinamensis (Perciformes: Lobotidae) in the western South Atlantic

Abstract: and follicle-stimulating hormone (FSH) were evaluated in all seasons. The histological analysis of the gonads showed that L. surinamensis is a multiple spawner with an asynchronous oocyte development. The gene expression of fshβ did not change throughout the reproductive cycle in males and females, while the gene expression of lhβ in males was higher in the summer compared to the autumn/winter periods. Plasma E 2 was higher in females and 11-KT in males during spring. Gonadal development, plasma level of E 2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This species can reach 1 m in length and 12 kg in weight. The compress and robust body is dark brown or blackish, while juveniles show yellowish shades; sexual dimorphism is not evident (Fagundes et al, 2021).…”
Section: Marco Albano and Claudio D'igliomentioning
confidence: 99%
“…This species can reach 1 m in length and 12 kg in weight. The compress and robust body is dark brown or blackish, while juveniles show yellowish shades; sexual dimorphism is not evident (Fagundes et al, 2021).…”
Section: Marco Albano and Claudio D'igliomentioning
confidence: 99%
“…In this sense, these dynamics of ovarian maturation studies in various teleost fish species can be assessed using distinct tools, as reported by Fagundes et al . (2021) and Honji et al . (2006), which use macroscopic and/or microscopic tools to assess these dynamics.…”
Section: Introductionmentioning
confidence: 97%
“…In this sense, these dynamics of ovarian maturation studies in various teleost fish species can be assessed using distinct tools, as reported by Fagundes et al (2021) and Honji et al (2006), which use macroscopic and/or microscopic tools to assess these dynamics. They include the differentiation of germ cells, changes in the germinal epithelium (Grier et al, 2009(Grier et al, , 2016 and analyses of the gonadal steroid hormone profile (Rajakumar and Senthilkumaran, 2020).…”
mentioning
confidence: 99%